Impact of obesity and diabetes on immune responses to SARS-CoV-2 in Bangladeshi adults - Ali, M (2024)
Overweight/obesity (Ov/Ob) and diabetes mellitus (DM) are known as independent risk factors for severe COVID-19 outcomes, which disproportionately affect the South Asian population. South Asians with a body mass index (BMI) of 27 kg/m2 have the same risk of COVID-19 mortality as white ethnicities at a BMI of 40 kg/m2.